A study on inflation adjusted gold investment in Malaysia / Eng Wat Kim and Syazwani Musa - Wat Kim, Eng; Musa, Syazwani (2013)
As gold price surges in the recent years, gold investment becomes popular in Malaysia and is driven by speculation. The purpose of this project is to determine whether gold is a suitable long term investment after accounted for inflation and to compare the performance of gold investment at different timing. The scope of this study is on yearly inflation adjusted gold price in Malaysia from the year 1967 to the year 2011. Using Pearson's correlation it is found that there is a very weak negative correlation between rates of return and inflation. The study also indicates that the cumulative change in gold prices is significantly higher and is almost 17 times higher than cumulative inflation in year 2011. This means gold price rises faster and beats the corresponding rise in inflation. Least squares method is used to find the best straight line fitting for inflation adjusted gold price at different investment starting years. Overall, gold investment is a suitable long term investment even after accounted for inflation. Therefore, in general, inflation adjusted gold price goes up and this suggests that gold investment is good, at least in the long term. The results indicate that inflation adjusted gold price is positively correlated with time.